Case Study: Evaluation of Menstrual Cycle Changes and Anxiety in Mothers Who Are Family Planning Acceptors Using Injectable Contraceptives - Roslianti, Elis; Fitri, Amelia; Sunarni, Neli; Srinayanti, Yanti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Family planning is a health service that helps individuals and couples control fertility, prevent unplanned pregnancies, and determine the number and spacing of children. According to the World Health Organization (WHO), injectable contraceptives are the most widely used method globally, accounting for 35.3% of contraceptive users. Despite their effectiveness, injectable contraceptives are associated with side effects, including changes in the menstrual cycle, which can lead to anxiety among users. This case study aims to scientifically document nursing care for mothers using injectable contraceptives, focusing on the biological, psychological, social, and spiritual aspects. It emphasizes the importance of comprehensive nursing assessment, diagnosis, planning, intervention, evaluation, and documentation to support maternal and family health. The descriptive case study method was applied to explore changes in the menstrual cycle and anxiety in mothers using injectable contraceptives. Data collection involved interviews, physical examinations, observation, document review, demographic data, and quality of life questionnaires. Data validity was maintained using credibility, transferability, dependability, and confirmability criteria. Ethical considerations included informed consent, anonymity, and confidentiality. Data were analyzed systematically to identify key findings. Findings indicated that menstrual disturbances in mothers were linked to the hormonal effects of injectable contraceptives, specifically the impact of progesterone on the hypothalamic-pituitary axis, leading to suppression of ovulation and alteration of menstrual patterns. Nursing interventions contributed to a reduction in anxiety and improvement in menstrual regulation. Proper nursing care, guided by structured assessment and ongoing evaluation, can address anxiety and menstrual issues related to injectable contraceptive use. Continued documentation is essential for ensuring the effectiveness and continuity of care.